2016
DOI: 10.1051/0004-6361/201628446
|View full text |Cite
|
Sign up to set email alerts
|

Modelling the cosmic ray electron propagation in M 51

Abstract: Context. Cosmic ray electrons (CREs) are a crucial part of the interstellar medium and are observed via synchrotron emission. While much modelling has been carried out on the CRE distribution and propagation of the Milky Way, little has been done on normal external star-forming galaxies. Recent spectral data from a new generation of radio telescopes enable us to find more robust estimations of the CRE propagation. Aims. To model the synchrotron spectral index of M 51 using the diffusion energy-loss equation an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
57
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(68 citation statements)
references
References 69 publications
9
57
2
Order By: Relevance
“…Our best-fitting diffusion coefficients for µ = 0.5 are at least 2 orders of magnitude smaller than the values of a few 10 28 cm 2 s −1 that are found in the Milky Way and in other external galaxies for CREs with a few GeV, either from a spatial correlation analysis between the radio continuum emission and various star-formation tracers (e.g. Berkhuijsen et al 2013) or from a spectral index analysis as in this work Mulcahy et al 2016). The larger diffusion coefficients in spiral galaxies could be explained by their more ordered magnetic field structure, where the cosmic rays diffuse along magnetic field lines.…”
Section: Discussioncontrasting
confidence: 56%
“…Our best-fitting diffusion coefficients for µ = 0.5 are at least 2 orders of magnitude smaller than the values of a few 10 28 cm 2 s −1 that are found in the Milky Way and in other external galaxies for CREs with a few GeV, either from a spatial correlation analysis between the radio continuum emission and various star-formation tracers (e.g. Berkhuijsen et al 2013) or from a spectral index analysis as in this work Mulcahy et al 2016). The larger diffusion coefficients in spiral galaxies could be explained by their more ordered magnetic field structure, where the cosmic rays diffuse along magnetic field lines.…”
Section: Discussioncontrasting
confidence: 56%
“…The CRE diffusion length l diff ∝ (Dt CRE ) 1/2 , where D is the diffusion coefficient. Mulcahy et al (2016) found no evidence for an energy dependence of D in M 51 in a similar CRE energy range of our observations, hence we obtain for a synchrotron energy loss-dominated halo…”
Section: Frequency Dependence Of Radio Scale Heightssupporting
confidence: 65%
“…where the diffusion coefficient D depends on the energy as Strong et al (2007) found 0.3 µ 0.6 from modelling CRE propagation in the Milky Way, and Murphy et al (2012) found (for a star-forming region in the Large Magellanic Cloud) a strong energy dependence of D for CRs between ≈3 and 70 GeV, there are recent indications that the energy dependence may not be significant for CRE energies 10 GeV (Recchia et al 2016a;Mulcahy et al 2016). We therefore fitted for D 0 using different choices of µ, as stated below.…”
Section: Parametrisation Of Advection and Diffusion Modelsmentioning
confidence: 98%